Rectal and Urethro-Vesical Subregions for Toxicity Prediction After Prostate Cancer Radiation Therapy: Validation of Voxel-Based Models in an Independent Population - Mylona, Eugenia; Ebert, Martin; Kennedy, Angel; Joseph, David; Denham, James; Steigler, Allison; Supiot, Stephane; Acosta, Oscar; de Crevoisier, Renaud (International journal of radiation oncology, biology, physics, 2020)
Recent voxel-based studies have shown that the dose to specific rectal and urethro-vesical subregions is predictive of toxicities after prostate cancer intensity modulated radiation therapy. The objective of this study was to validate the discriminatory power of these subregions with respect to the whole organs in a large independent population. The validation cohort consisted of 450 patients from the TROG03.04-RADAR trial treated with 3-dimensional conformal radiation therapy at 66 to 74 Gy. Previous voxel-based analyses identified an inferoanterior rectal subregion as predictive of rectal bleeding and 5 subregions in the urethra and the posterior and superior part of the bladder as predictive of urinary incontinence, dysuria, retention, and hematuria. In the validation cohort, these subregions were segmented in each patient’s anatomy. Dose-volume histograms (DVHs) of the whole organs and the 6 subregions were compared bin-wise between patients with and without toxicities. The discriminatory power of DVHs for grade ≥2 toxicity endpoints was assessed using the area under the receiver operating characteristic curve (AUC). Subregion DVHs were significantly different between patients with and without toxicities for late rectal bleeding (V44-V74), acute urinary incontinence (V68-V72), late dysuria (V56-V68), and late retention (V14-V64). The dose to the rectal subregion and the whole rectum were equally predictive of rectal bleeding (V68; AUC = 0.61). The doses to 3 out of the 5 urethro-vesical subregions were found to be more predictive than the dose to the whole bladder: in the urethra for acute incontinence (V71 AUC = 0.69 vs V71 AUC = 0.66), in the posterior part of the bladder for late dysuria (V65 AUC = 0.66 vs V68 AUC = 0.59), and late retention (V39 AUC = 0.74 vs no significant AUC). Three subregions located in the urethra and the bladder were successfully validated as more predictive of urinary toxicity than the whole bladder for urinary incontinence, retention, and dysuria. Sparing the posterior part of the bladder in particular in treatment planning may reduce the risk of late urinary retention.